CD15, CD30, and PAX5 evaluation in Hodgkin's lymphoma on fine‐needle aspiration cytology samples. Issue 3 (11th December 2019) - Cozzolino, Immacolata; Vitagliano, Giulio; Caputo, Alessandro; Montella, Marco; Franco, Renato; Ciancia, Giuseppe; Selleri, Carmine; Zeppa, Pio
Abstract: Background: The phenotypical identification of diagnostic cells is crucial for the diagnosis of Hodgkin's lymphoma (HL) on fine‐needle aspiration cytology (FNAC). The aim of this study is to evaluate the immunocytochemical (ICC) expression of CD30, CD15, and PAX5 in Hodgkin's cells (HC) and Reed‐Sternberg cells (RSC) on smears and cell‐blocks (CB) of HL and to compare the performance of each antibody on smears and CB. Methods: In 21 FNAC cases of histologically confirmed classical HL, ICC identification of HC and RSC was performed using CD15, CD30, and PAX5 on smears and CB, respectively. Results: CD30 was positive in 19/21 cases (90.5%; 11/11 smears and 8/10 CB), CD15 was positive in 14/21 cases (66.7%; 5/11 smears and 9/10 CB), and PAX5 was positive in 13/21 cases (61.9%; 9/11 smears and 4/10CB). Conclusions: CD15, CD30, and PAX5 are useful to the FNAC identification of HC and RSC. CD30 is the most sensitive, followed by CD15 and PAX5, which are more effective on CB and smears, respectively.